Effectiveness of the Parole Program in Overcoming Inmate Overcapacity in Bekasi Class II A Correctional Institutions - Arif, Wahyu; Hartini, Sri; Fajri, Ibrahim (Universitas Ibn Khaldun Bogor, 2024)
The granting of parole to prisoners at the Class II A Bekasi Correctional Institution has been carried out in accordance with Regulation of the Minister of Law and Human Rights Number 7 of 2022 concerning Terms and Procedures for Granting Remission, Assimilation, Leave to Visit Family, Parole, Leave Ahead of Release, and Conditional Leave. But apart from that, there are also several prisoners who have met the requirements in accordance with the Regulation of the Minister of Law and Human Rights Number 07 of 2022 concerning Terms and Procedures for Granting Remission, Assimilation, Leave to Visit Family, Parole, Leave Ahead of Release, and Conditional Leave, but have not been released due to several inhibiting factors. One of the inhibiting factors is due to the large number of files that must be prepared and sometimes do not follow in accordance with predetermined procedures. The implementation of the granting of parole by Class II A Bekasi Correctional Institution is considered successful, because it can be seen from the comparison of parole data at Class II A Bekasi Correctional Institution for the 2019-2022 period between those proposed and those realized close to the proposed amount